Morphology control of BiFeO3 aggregates via hydrothermal synthesis. (21st January 2016) - Suzuki, Kazumasa; Tokudome, Yasuaki; Tsuda, Hiroshi; Takahashi, Masahide
Abstract : Morphology‐controlled BiFeO3 aggregates composed of oriented building units were prepared by a simple one‐pot hydrothermal synthesis without any additives. The shape of the building units, the size distribution of the aggregates and the internal structure of the aggregates were controlled by the supersaturation condition of the precursor solution, and the formation mechanism of the aggregates is discussed on the basis of these structure analyses. Abstract : The assembly of crystalline building units with specific shape‐derived properties into aggregates is often required to broaden their practical applications because the properties of the building units can be fully integrated and used in the aggregates owing to their orientation. Herein, morphology‐controlled BiFeO3 aggregates composed of oriented crystalline building units were fabricated via a hydrothermal process without any additives, and the effects of the supersaturation conditions on the aggregation state were investigated. The supersaturation condition, controlled by varying the KOH concentration, was found to affect the shape of the crystalline building units. For lower supersaturation conditions, the morphology of the aggregates was found to be closely related to the shape of the fundamental building units, and the results indicated that oriented attachment occurred between specific crystal faces of the building units. Under a high supersaturation condition, the morphology of the aggregate did not reflect the shape of the building units and a monodispersed spherical aggregate was obtained. Further, the internal microstructures of the aggregates changed from homogeneous and dense to sparse core and dense shell structures with an increasing supersaturation condition. The formation mechanism of these morphology‐controlled aggregates is discussed using microstructure analyses. The present approach to control the morphology of aggregates using the shape of the building units and aggregation kinetics could also be applicable for other microcrystalline aggregated systems in addition to BiFeO3 .